2000
DOI: 10.1074/jbc.m002839200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an Unusually Long Operator for the Fur Repressor in the Aerobactin Promoter of Escherichia coli

Abstract: Production of the siderophore aerobactin in Escherichia coli is transcriptionally metalloregulated through the iron-dependent binding of the Fur (ferric uptake regulator) to a large region (>100 base pairs) within the cognate promoter in the pColV-K30 plasmid. We show in this article that such an unusually long operator results from the specific addition of degenerate repeats 5-NAT(A/T)AT-3 and not from a fortuitous occupation of the DNA adjacent to the primary binding sites by an excess of the repressor. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 37 publications
6
46
1
1
Order By: Relevance
“…Thus, in each of these cases, the binding affinity of a TF for the auxiliary site is adapted in order to reach an optimal TF concentration dependence of the response. Experimental support for these results comes from E. coli cis-regulatory regions containing homocooperative LysR family activator binding sites and others containing homocooperative Fur repressor binding sites, which have both been studied in some detail and confirm the role of strong and weak binding sites proposed by the model (80,165,318). Therefore, in the case that multiple TFBSs for a single TF are present in a promoter, the secondary sites are expected to be more conserved than the primary TFBS in the case of activators and the other way around in the case of repressors.…”
Section: Cooperative and Competitive Dna Binding And Motif Stringencysupporting
confidence: 52%
“…Thus, in each of these cases, the binding affinity of a TF for the auxiliary site is adapted in order to reach an optimal TF concentration dependence of the response. Experimental support for these results comes from E. coli cis-regulatory regions containing homocooperative LysR family activator binding sites and others containing homocooperative Fur repressor binding sites, which have both been studied in some detail and confirm the role of strong and weak binding sites proposed by the model (80,165,318). Therefore, in the case that multiple TFBSs for a single TF are present in a promoter, the secondary sites are expected to be more conserved than the primary TFBS in the case of activators and the other way around in the case of repressors.…”
Section: Cooperative and Competitive Dna Binding And Motif Stringencysupporting
confidence: 52%
“…This sequence is followed by the hexamer GATAAG that closely resembles the minimal interaction unit NAT(A\T)AT, which was recently reported as the nucleotide array that can explain the iron-regulated expression of AT-rich promoters that do not contain canonical Fur boxes (Escolar et al, 1999). Furthermore, at least 10 other units very similar to those found in the aerobactin promoter region (Escolar et al, 2000) can be identified upstream of the adhC1 initiation codon. This region also includes the sequence TAGCATTACAT-TATCTATTTTGCT that matches 19 of the 24 nucleotides found in the non-template strand of the Furbinding site I of the promoter region of the fatDCBA operon of the pJM1 plasmid (Chai et al, 1998).…”
Section: Regulation Of the Expression Of Adhcmentioning
confidence: 91%
“…For example, the two cooperative Fur-binding sites that overlap the core promoter on the pColV-K30 plasmid are supported by an array of low-affinity auxiliary sites [29]. A second example is the duo of dnaA promoters, 1P and 2P [40].…”
Section: Homo-cooperative Auxiliary Sites Provide Steep Responsesmentioning
confidence: 99%